Exploration and Inventory of Epiphytic Plants in the Forest of Lemor Botanical Gardens, Suela District, Lombok Island - Nabila, Elva Elvina; Zulkifli, Lalu; Raksun, Ahmad; Mertha, I Gde (Jurnal Biologi Tropis, 2025)
Various types of plants are found in Lemor Botanical Garden Forest (located in Suela Village, East Lombok Regency), one of which is epiphytic plants. Epiphytic plant are plants that live attached to other plants. This study aims to determine the types of epiphytic in the Lemor Botanical Garden Forest and the most dominating epiphytic species based on the environmental characteristics of the Lemor Botanical Garden Forest. This research is a descriptive research. Data collection was carried out using the cruisi method from October to November 2024. Data were analyzed qualitatively. The results showed that in the Lemor Botanical Garden Forest, 15 species of epiphytic were found consisting of 8 families and 797 individuals.  The types of epiphytic found include: Grosourdya appendiculata, Nephrolepis exaltata, Microlepia todayensis, Goniophlebium verrucosum, Goniophlebium persicifolium, Drynaria quercifolia, Drynaria sparsisora, Pyrrosia eleagnifolia, Pyrrosia longifolia, Microsorum punctatum, Cryptogonium phyllogonioides, Thuidium glaucinoides, Rhaphidophora pinnata, Syngonium podophyllum, and Piper betle. The most dominating epiphytic species based on the environmental characteristics of Lemor Botanical Garden Forest are epiphytic found growing in the watershed many as 13 species, 3 of which are: Drynaria quercifolia, Microsorum punctatum, and Rhaphidophora pinnata, with a percentage of 37%. The most dominant species found was Drynaria quercifolia from the Polypodiaceae family with 148 individuals.